Law for Insurers in Spain and Portugal - Ruiz Rodríguez, Segundo (Colección de libros electrónicos de ULoyola, 2017)
This book is an in depth study of some difficult and specific legal subjects which are key in the development of insurance business in Spain and Portugal, such as: insurance contract, regulatory law, information requirements before and after the conclusion of the contract, nomination of person/s to benefit from a policy, Spanish life and non life insurance taxation, Registry of insurance policies covering death risk, prevention of money laundering, etc. It is based on several reports that LEGSE Abogados has prepared over a period of 25 years, responding to some habitual questions asked by non Spanish/Portuguese insurance companies, clients of this law firm. We hope this book will prove to be a useful guide.